ILLEGAL FINANCIAL SERVICE BUSINESS AND ACCOUNTING PRACTICE IN PASAR BESAR MALANG - DHANIAS, FITRIANA RAKHMA; Ludigdo, Unti; Mulawarman, Aji Dedi (Accounting Department,, 2016)
Originated from the rapid flow of commerce accompanying the economic development ranging from macro to micro sectors, impacts on the large amount of available capital options. This phenomenon indicates that not only financial services such as banking, Public Loan Bank (Bank Perkreditan Rakyat), and cooperation exist, but also illegal financial services, which enliven capital activities amongst traditional market merchants. This research aims to explore the existence of accounting in illegal financial service business in Pasar Besar Malang. The researchers use ethnomethodology as the research method as it has more points in understanding empirically. Ethnomethodology is an empirical study which learns how humans catch and carry out their daily activities within a social reality. The result of this research finds that accounting does exist in illegal financial service business in Pasar Besar Malang where the presence of accounting in loansharks business practice is also influenced by local values of Javanese culture.Â